(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study is to investigate the effects on ovarian tissues of adult female rats, which were the offspring of rats administered acrylamide (AA) and vitamin E during pregnancy.Material and Methods: Thirty rats were divided into 5 groups of 6 pregnant rats, as the Control, Corn Oil, Vitamin E, AA, Vitamin E + AA groups. The births were monitored on the 21st day to select the female rats. The selected female rats were decapitated at the end of the 8th week and their ovarian tissues were removed under anesthesia malondialdehyde (MDA), reduced glutathione (GSH), total antioxidant capacity (TAS), total oxidant capacity (TOS), oxidative stress index (OSI), superoxide dismutase (SOD), catalase (CAT) and nitric oxide (NO) levels were examined.Results: Administration of AA during pregnancy caused an increase in MDA, TOS, OSI and NO levels and a decrease in GSH, SOD, CAT and TAS levels in the ovarian tissues of the rats when compared to the control group. It was determined that vitamin E administration caused an increase in GSH, SOD, CAT and TAS levels in ovarian tissues, compared to all other groups (P 0.05).Conclusion: Exposure to food-induced AA toxicity increases each day and the parallel increase in infertility suggests that it could be related to AA toxicity. Although vitamin E is capable to exert a protective effect against AA toxicity through increasing the antioxidant capacity of ovarian tissue, there is certain necessity for further studies.Keywords: Pregnancy; acrylamide; vitamin E; oxidative stress; infertility; ovarian tissue.